2020
DOI: 10.1002/mus.26898
|View full text |Cite
|
Sign up to set email alerts
|

Daily grip strength response to intravenous immunoglobulin in chronic immune neuropathies

Abstract: Introduction Monitoring grip strength at home may detect improvement between intravenous immunoglobulin (IVIg) treatments in patients with chronic inflammatory neuropathies (CINs). Methods Fifteen patients recorded grip strength each day, from one IVIg treatment until the next. We analyzed grip strength changes comparing thresholds of 8 kPa and 14 kPa. “Random” fluctuations of grip strength were distinguished from treatment response by smoothing the data. Results “Random” fluctuations of at least 8 kPa occurre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 21 publications
0
24
1
Order By: Relevance
“…12 Especially when rolling 5-day mean grip strength values are calculated, changes of ≥8 kPa may be clinically meaningful and capable of distinguishing between treatment response and random day-to-day grip strength fluctuations. 13 While both absolute and relative cutoffs may have a role in detecting a clinically meaningful change, we elected a percentage approach because it contextualizes the degree of change proportional to the patient's baseline strength. By using these parameters, we were able to identify a population of patients with frequent IVIGassociated TRFs and another population who were stable over multiple treatment cycles.…”
Section: Discussionmentioning
confidence: 99%
“…12 Especially when rolling 5-day mean grip strength values are calculated, changes of ≥8 kPa may be clinically meaningful and capable of distinguishing between treatment response and random day-to-day grip strength fluctuations. 13 While both absolute and relative cutoffs may have a role in detecting a clinically meaningful change, we elected a percentage approach because it contextualizes the degree of change proportional to the patient's baseline strength. By using these parameters, we were able to identify a population of patients with frequent IVIGassociated TRFs and another population who were stable over multiple treatment cycles.…”
Section: Discussionmentioning
confidence: 99%
“…Our study used three different outcome measures along with MCID based cut-off values to define improvement. We recognize that these criteria do not always reflect clinical practice and that a less static, more patient-tailored assessment may be more suitable to define meaningful improvement and treatment (non) responders [47,[49][50][51]. We advocate a multimodal approach in those patients with expected limited improvement, for example in patients with severe axonal damage at presentation or those with only minimal disability or impairment, if treatment is considered justified at all.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that the daily self-monitoring of GS demonstrated improvement after IVIg in some patients with CINs that may be indicative of treatment dependency, although this was not prospectively confirmed. 11 In this study,…”
Section: Introductionmentioning
confidence: 87%
“…9,10 This figure was confirmed by a recent study showing that random fluctuations ≥8 kPa occurred in 27% of patients. 11 It is also uncertain whether frequent measurements with outcome measures may provide useful information to guide clinical decision on adjustment of treatment. A recent study showed that the daily self-monitoring of GS demonstrated improvement after IVIg in some patients with CINs that may be indicative of treatment dependency, although this was not prospectively confirmed.…”
Section: Introductionmentioning
confidence: 99%